(untitled) - Chang, Kang-Tsung (Boston, 2006)
This book is designed to provide students in a first or second GIS course with a solid foundation in both GIS concepts and the use of GIS. The book retains the same comprehensive coverage of GIS topics as featured in the first edition. This edition is organized into five parts. Part 1 (Chapters 1 to 7) explains the fundamentals of GIS including coordinate systems, data models, data input, spatial data editing, and attribute data management. Part 2 (Chapters 8 and 9) includes data display and data exploration. Part 3 (Chapters 10 and 11) examines the basic tools for GIS analysis and their applications. Part 4 (Chapters 12 and 13) covers terrain mapping and analysis, and spatial interpolation. Part 5 (Chapters 14 to 16) deals with GIS models and modeling, regions, and network and dynamic segmentation.
Keywords: Geographic information systems,Hệ thống thông tin địa lý